Pengaruh Kemutakhiran Teknologi, Kemampuan Teknik Personal Sistem Informasi, Program Pelatihan Pengguna Dan Dukungan Manajemen Puncak Terhadap Kinerja Sistem Informasi Akuntansi - Joshua Dharmawan; Jimmy Ardianto (Ultima Accounting : Jurnal Ilmu Akuntansi, 2017)
The objective of this research to test, examine and to provide empirical evidence to the influence of technology sophistication, personal technical ability of information systems, user training program and top management support to the performance of accounting information system. The research was conducted using a survey method to to provide the questionnaires to the employees in retail consumer goods company. Data used in this study was primary data, id est: questionnaires. The respondents in this study were 102 who are employees which use accounting information system. Data analysis techniques in this study using multiple linear regression. The results of this study were (1) technology sophistication had a significant influence toward the performance of accounting information system; (2) personal technical ability of information systems had no significant influence toward the performance of accounting information system; (3) user training program had a significant influence toward the performance of accounting information system; (4) top management support had a significant influence the performance of accounting information system. Keywords: accounting information system, personal technical ability, technology sophistication, top management support and training program